Литургическая музыка русских композиторов для хора без сопровождения - Левандо П. (Логосвос, 2003)
Экземпляры: БС (20170911) / Инвентарный номер: РТШ49895 / Сис.шифр: 85 / Авт.знак: Л 64 / ГРНТИ: 18.41 / ББК: 85.314